Some Microeconomics of Fiscal Deficit Reductions : The Case of Tax Expenditures. (IMF Working Papers; Working Paper ;, 1989)
This paper considers the merits of reducing or eliminating some specific tax expenditure measures currently in force in the United States with a view to reducing the federal fiscal deficit. The paper starts from the observation that savings decisions in the United States are distorted and that therefore government borrowing to finance current expenditures results in significant welfare losses. It is possible by reducing or eliminating individual tax expenditures to reduce the fiscal deficit while at the same time enhancing economic efficiency. However, tax expenditures are heterogeneous so changes to the range of tax expenditures should be selective.